Yield Evaluation of Selected Clones Apomictic Iles-Iles (Amorphophallus muelleri Blume) on Second Growing Period - Lontoh, Adolf Pieter; Santosa, Edi; Kurniawati, Ani; Sari,; Maryati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Increasing corm production of iles-iles (Amorphophallus muelleri Blume) through genetic improvement is important for increasing farmers’ income. However, the study on variety development is rarely reported. Here, yield evaluation of the second growing period was conducted at IPB Experimental Station Leuwikopo Farm, Bogor, Indonesia (-6.5647419, 106.7220331, 17.25z) from August 2017 to July 2018 in order to select candidate clone with high corm production. One-year-old corms of 21 F1 accessions were planted under 55% shading net with four replications. The parent population was set as a control. Results showed that accessions exhibited variation in corm size. The parent population produced corm ranged 622.3-908.3 g in weight (on average 764.2 g). The pooled accessions produced corm 180.7-1527.5 g in weight, corm diameter 71.0-145.8 mm, and corm height 46.6-87.6 mm. Nine accessions produced 5.91-99.88% higher average corms weight than the parent, i.e., BKB, BS, CF, CK, CR, DPG, DPP, SBM, and SHJ. Based on 30% as the basis of corm weight improvement, we concluded that five accessions, i.e., CK, CR, DPG, DPP, and SBM as prospective candidate clones. These accessions could be further evaluated in the third growing period to select best candidates of new variety of A. muelleri.Keywords: Agamosporous, Araceae, breeding strategy, new variety, productivity